Walkability Index for Elderly Health: A Proposal - Fernando Brandão Alves (2020)
Nowadays, the elderly tend to make more trips: Health benefits resulting from their daily walking routines are an important topic in the context of urban renewal processes. Many health organizations and researchers have demonstrated the influence of the urban environment on walkability levels. This article aims to design a multifactor Walkability Index for Elderly Health (WIEH), capable of associating both the adequacy level of public spaces to elderly walkability, and physical exercise benefits while walking. The methodological approach comprised two main parts: Firstly, a literature review of main reports, legislation, and scientific articles was conducted at the intersection of 'gerontology and physical exercise' with 'urban design and mobility', leading to the selection of four aging-related studies as main contributors to the design of the WIEH; and, secondly, the development of the WIEH was undertaken, based on two premises and designed according to four steps. The first premise defined three systematic areas (urban tissue, urban scene, and safety), variables, and criteria to classify the pedestrian network; and the second premise focused on slopes and stairs in public spaces. The WIEH is divided in four steps: (1) Analyzing public spaces and characterizing their quality for walking, (2) considering the existence of slopes and stairs, (3) calculating different routes for the elderly in their daily routines, or when going to points of interest, and (4) selecting the "heart-friendly route" for elderly people. Adequate walking paths for the elderly can be identified through this innovative approach, with the aim of achieving direct health benefits during their daily routines. Ultimately, the WIEH is capable of supporting decision makers and designers in creating inclusive and age-friendly spaces.